Nutritional Imbalance – Dominant Consumption Behaviour of Young People from Romania - Dorin Vicenţiu Popescu; Lelia Voinea; Mihai Teodor Negrea (Amfiteatru Economic Journal, 2015)
The alert lifestyle, the great availability and accessibility of foodstuff and the powerful pressure exercised by the food industry by means of mass-media, in order to encourage overconsumption, have disturbed all the elements of food consumers' behaviour, causing them to miss the nutritional landmarks obtained within family education. Adopting a diet based on quantity instead of quality, due to a bad nutritional education, the modern consumers are both overfed and underfed, two features rarely found in the same body throughout the history. In this context, in order to prevent the nutrition and metabolic disorders, there is the need, more than ever before, of awareness for connecting nutrition and health ("you are what you eat") and the necessity to adopt especially by the new generation of consumers, the basic principles of a balanced diet. With the main aim to highlight the characteristics of food consumption behaviour for the new generation of Romanian consumers, the authors carried out an exploratory research, based on the technique of the food diary through estimation. As for highlighting the potential nutritional imbalances, the authors analysed the medium allowance of energy and macronutrients of the respondents' diet. Also, it would be a fulfilment that the research results to lead to the subsequent elaboration of a guide for redirecting the food behaviour of young consumers, in order to avoid the nutritional imbalances and to prevent serious illnesses.
Keywords: I12; O13; Z10; 330; new generation of consumers; eating behaviour; energy intake; guideline daily amounts; nutritional imbalance